Pengembangan Desain Kurikulum Berbasis MBKM untuk Meningkatkan Mutu Pembelajaran Program Studi PGMI - Annisa, Choirul; Triani, Dewi Agus (SITTAH: Journal of Primary Education, 2024)
Curriculum development in educational institutions is essential to meet the demands of a dynamic education system and enhance the quality of learning. The Merdeka curriculum aims to prepare students to contribute maximally to society by equipping them with skills and a creative mindset. This research aims to develop and evaluate the design of the MBKM curriculum in the PGMI Study Program. The research method used is Research and Development, with the development design referring to the Borg and Gall model. The results of this study are a Semester Learning Plan (RPS) integrated with the MBKM curriculum for the PGMI Study Program, as well as an elaboration on the processes and outcomes of the curriculum development that supports the achievement of learning objectives.